The Theme of Resistance in the Writings of Algirdas Landsbergis, Vytautas Alantas and Vincas Ramonas - Kuizinienė, Dalia (Genocidas ir rezistencija, 2000)
During the period 1950–1960 the theme of the Soviet and German occupations, war and the loss of the homeland predominates in the works of Lithuanian émigré writers. A number of novels, stories and short stories devoted to the subject were written and published by Lithuanian writers abroad. The same themes prevailed in the works of playwrights too. In the middle of the Sixties émigré writers produced a number of prominent memoirs.Ramonas' novel Dust in the Red Sunset (Dulkės raudonam saulėleidy) and Alantas' novel In the Glow of Hell (Pragaro pošvaistės) deal with the problem of moral self-determination facing extreme historical situations. In the first novel the scene is set during the Soviet occupation, in the other during the German occupation. The main characters of both novels encounter the problem of choice between collaboration or active resistance against occupation. The positive characters in the novels are to a great extent idealized and romanticized, and the structures of the novels are rather loose. The novels Dust in the Red Sunset and In the Glow of Hell can be characterized as novels of thesis.The play Five Poles in the Market-place (Penki stulpai turgaus aikštėje) by Landsbergis, a representative of the younger generation, is considered one of the most original émigré works. Based on the model of modern Western drama, the play depicts the last years of active resistance in Lithuania. Using a number of rich symbols the meaning of which change throughout the play, the author reveals the drama of the fight for freedom in any totalitarian society. imparting a universal character to it. Transposing the problem of ideological conflict to the level of human existence, the author universalised the subject of resistance. The play is one of the few émigré works that has won international recognition, and has been staged by U.S.A and Canadian theatre companies.
Keywords: emigree; literature; Algirdas Landsbergis; Vytautas Alantas; Vincas Ramonas